2003
DOI: 10.1093/oxfordjournals.schbul.a006997
|View full text |Cite
|
Sign up to set email alerts
|

Who Are Patients on Conventional Antipsychotics?

Abstract: The advent of atypical antipsychotics presented psychiatrists with an effective way of treating psychosis without the many side effects associated with conventional agents. Given the superiority of atypical antipsychotics, we examined demographic information and treatment histories of patients currently treated with conventional antipsychotics, especially in regard to treatment with atypical agents. Medication histories and demographic information for 276 patients admitted to an urban hospital were obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Higher use of first-generation antipsychotics among African-American patients compared with Caucasian patients has been previously documented (11,12). The only first-generation antipsychotic examined, haloperidol, was more likely than olazapine, quetiapine, or valproic acid to be prescribed among African-American patients (p=.009, p=.01, and p=.001, respectively, in post hoc tests).…”
Section: Discussionmentioning
confidence: 62%
“…Higher use of first-generation antipsychotics among African-American patients compared with Caucasian patients has been previously documented (11,12). The only first-generation antipsychotic examined, haloperidol, was more likely than olazapine, quetiapine, or valproic acid to be prescribed among African-American patients (p=.009, p=.01, and p=.001, respectively, in post hoc tests).…”
Section: Discussionmentioning
confidence: 62%
“…Studies in the US have concluded that ethnic minority patients are less likely to be prescribed atypical antipsychotics relative to the general population (Opolka, Rascati, Brown, & Gibson, 2004;Valenti, Narendram, & Pristach, 2003). It may be the case that similar discrimination occurs against older schizophrenia and schizoaffective disorder patients.…”
Section: Agementioning
confidence: 99%
“…They report generally consistent findings. With few exceptions, AAs in these samples have a lower likelihood of receiving atypical versus conventional antipsychotics (Copeland, Zeber, Valenstein, & Blow, 2003;Herbeck et al, 2004;Kreyenbuhl, Zito, Buchanan, Soeken, & Lehman, 2003;Mark, Palmer, Russo, & Vasey, 2003;Opolka, Rascati, Brown, Barner, et al, 2003;, 2004Valenti, Narendran, & Pristach, 2003); they receive significantly higher antipsychotic doses (Diaz & De Leon, 2002;dosReis, Zito, Buchanan, & Lehman, 2002;Valenstein et al, 2004); and they are more likely to receive diagnoses of schizophrenia versus affective disorders (Barnes, 2004;Butterfield et al, 2004;Mathews, Glidden, & Hargreaves, 2002;Neighbors, Trierweiler, Ford, & Muroff, 2003;Strakowski et al, 1996;Strakowski et al, 2003;Trierweiler et al, 2000). However, it is difficult to distinguish the specific influence of race on disparate outcomes from other factors that may characterize acute care samples.…”
mentioning
confidence: 99%